Gamma-ray imaging performance of the GRI+ Compton camera. (14th September 2021) - Caffrey, A.; Harkness-Brennan, L.J.; Alshammari, H.; Boston, A.J.; Boston, H.C.; Griffiths, O.; Judson, D.S.; Kalantan, S.; Le Crom, B.; Nolan, P.J.; Powell, A.; Platt, J.; et al.
Abstract: GRI+ (Gamma-Ray Imager) is a cart-based Compton camera developed at the University of Liverpool. The system comprises three electrically-cooled semiconductor detectors; two planar double-sided strip detectors (Si(Li) and HPGe) and an HPGe coaxial detector. The mobile cart houses the necessary components for data acquisition and analysis, providing complete functionality for imaging gamma-ray sources in an industrial setting. This paper reports on the operation of the system and the methods used to improve intrinsic system performance. The processing chain for extracting information pertaining to gamma-ray interactions has been developed and the imaging performance is characterised using an analytical reconstruction code. The obtainable Angular Resolution Measure (ARM) from a Cs-137 point source placed 10.5 cm from the front of the Si(Li) cryostat was determined to be 4.12 ∘ after the application of data processing techniques. The system energy resolution, which is key to isotope identification and image quality, was calculated to be less than 0.5% at 1332.5 keV.